The statute of the real in Lacan: from the first writings to the VII seminar - the psychoanalysis’ ethics - Chaves, Wilson Camilo (Paidéia (Ribeirão Preto), 2006)
This article seeks to elucidate the notion of Real in Lacan, from the first writings to the VII seminar, Psychoanalysis' Ethics. Initially, are privileged Imaginary and Real; Symbolic and Real; Symbolic, Imaginary and Real. After their elucidation, it is advanced to the transition of the Real concept, re-doing the course fron Seminars to referring texts. In the VII Seminar, dedicated to the Psychoanalysis' Ethics, the relations between the Real and das Ding are glimpsed. The Real is seen as from the Thing order. The work is concluded affirming that Lacan, later, will formulate the Real as belonging from the impossible order.